Rosmarinic Acid Intravitreal Implants: A New Therapeutic Approach for Ocular Neovascularization - Vieira, Lorena Carla; Moreira, Carolina Paula de Souza; Castro, Brenda Fernanda Moreira; Cotta, Oliver Araújo Lacerda; Silva, Luciana Maria; Fulgêncio, Gustavo de Oliveira; Silva-Cunha, Armando; Fialho, Sílvia L. (Planta Medica, 2020)
Rosmarinic acid, a plant-derived compound with antiangiogenic activity, can be applied for the treatment of ocular diseases related to neovascularization, such as diabetic retinopathy, macular edema, and age-related macular degeneration. These diseases represent the leading causes of blindness worldwide if they are not properly treated. Intravitreal devices allow for localized drug delivery to the posterior segment, increasing the drug bioavailability and promoting extended release, thus, reducing side effects and enhancing the patientʼs compliance to the treatment. In this work, rosmarinic acid-loaded poly lactic-co-glycolic acid intraocular implants were developed with a view for the treatment of ocular neovascularization. Physical-chemical, biocompatibility, and safety studies of the implants were carried out in vitro and in vivo as well as an evaluation of the antiangiogenic activity in a chorioallantoic membrane assay. Data obtained showed that rosmarinic acid released from the implants was quantified in the vitreous for 6 weeks, while when it was in the solution formulation, after 24 h, no drug was found in the vitreous. The delivery device did not show any sign of toxicity after clinical evaluation and in electroretinographic findings. Histological analysis showed normal eye tissue. Rosmarinic acid released from implants reduced 30% of new vesselʼs formation. The intravitreal implant successfully allowed for the prolonged release of rosmarinic acid, was safe to rabbits eyes, and demonstrated activity in vessel reduction, thus demonstrating potential in preventing neovascularization in ophthalmic diseases.
Keywords: rosmarinic acid; implants; intravitreal; drug delivery; neovascularization; safety